2012
DOI: 10.1037/a0028485
|View full text |Cite
|
Sign up to set email alerts
|

Improving delayed face recognition in Alzheimer's disease by differential outcomes.

Abstract: These findings demonstrate, to our knowledge for the first time, that face recognition memory in patients with Alzheimer is improved when differential outcomes are used and draw attention to the potential of this procedure as a therapeutic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 36 publications
8
29
0
2
Order By: Relevance
“…These data are consistent with those of others who have shown deficits in DMTS task performance in participants with an AD diagnosis (Fowler et al, 2002;Money et al, 1992;Plaza et al, 2012;Sahakian et al, 1988;Sano et al, 1995). Notable aspects of DMTS task performance seen here in persons with a diagnosis of AD include significantly reduced speed of responding to both the sample stimuli (during which time processes such as encoding and discrimination should be important) and the choice stimuli (which should reflect functions perhaps more related to recall).…”
Section: Short-term Nonverbal Memorysupporting
confidence: 91%
“…These data are consistent with those of others who have shown deficits in DMTS task performance in participants with an AD diagnosis (Fowler et al, 2002;Money et al, 1992;Plaza et al, 2012;Sahakian et al, 1988;Sano et al, 1995). Notable aspects of DMTS task performance seen here in persons with a diagnosis of AD include significantly reduced speed of responding to both the sample stimuli (during which time processes such as encoding and discrimination should be important) and the choice stimuli (which should reflect functions perhaps more related to recall).…”
Section: Short-term Nonverbal Memorysupporting
confidence: 91%
“…To our knowledge, this is the first time that such an effect has been reported in 7-year-old children. Some recent studies have shown that the DOP is effective in improving memory-based performance after short delays in normal aging, in young people, and in patients with alcohol-related amnesia and Alzheimer's disease (Hochhalter et al, 2000;López-Crespo et al, 2009;Martella et al, 2012;Plaza et al, 2011Plaza et al, , 2012. All these results can be explained according to the model suggested by Savage and colleagues (e.g., Overmier, Savage, & Sweeney, 1999;Ramirez, Buzzetti, & Savage, 2005;Savage, 2001;Savage & Parsons, 1997), who proposed that there are two different memory systems that are activated by differential and nondifferential outcomes.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, they found that three patients with alcohol-induced amnesia showed significantly better delayed face recognition when differential outcomes were arranged. Later on, the potential of the DOP for aiding human memory has also been evident in four studies conducted with young people (Martella, Plaza, Estévez, & Fuentes, 2012;Plaza, Estévez, López-Crespo, & Fuentes, 2011), with older adults (López-Crespo, Plaza, Fuentes, & Estévez, 2009), and with Alzheimer's disease patients (Plaza, López-Crespo, Antúnez, Fuentes, & Estévez, 2012). In these studies, delayed face recognition performance of participants was improved by pairing each correct response with a specific outcome.…”
Section: Introductionmentioning
confidence: 93%
“…The benefits of using the DOP also have been observed in people with discriminative learning difficulties, such as those with Down's syndrome (Estévez, Overmier, Fuentes, & González, 2003), adults with Prader-Willi syndrome (Joseph, Overmier, & Thompson, 1997), or children born prematurely (Martínez et al, 2012). Further studies have demonstrated that the DOP is effective at improving memory-based performance in healthy children (Martínez, Estévez, Fuentes, & Overmier, 2009;Martínez, Flores, González-Salinas, Fuentes, & Estévez, 2013), young adults (Martella, Plaza, Estevez, Castillo, & Fuentes, 2012;Plaza, Estévez, López-Crespo, & Fuentes, 2011), and older adults (López-Crespo, Plaza, Fuentes, & Estévez, 2009), as well as individuals with memory-based deficits, such as Korsakoff's syndrome (Hochhalter, Sweeney, Bakke, Holub, & Overmier, 2000) or Alzheimer's disease (Plaza, López-Crespo, Antúnez, Fuentes, & Estévez, 2012). It is of some interest to note that selfassociation has been shown to improve memory in patients with severe amnesia .…”
mentioning
confidence: 99%